Nutrient‐related changes in the toxicity of field blooms of the cyanobacterium, Cylindrospermopsis raciborskii. Issue 1 (12th May 2014) - Burford, Michele A.; Davis, Timothy W.; Orr, Philip T.; Sinha, Rati; Willis, Anusuya; Neilan, Brett A.
Abstract Nutrients have the capacity to change cyanobacterial toxin loads via growth‐related toxin production, or shifts in the dominance of toxic and nontoxic strains. This study examined the effect of nitrogen (N) and phosphorus on cell division and strain‐related changes in production of the toxins, cylindrospermopsins (CYNs) by the cyanobacterium, Cylindrospermopsis raciborskii. Two short‐term experiments were conducted with mixed phytoplankton populations dominated by C. raciborskii in a subtropical reservoir where treatments had nitrate (NO3), urea (U) and inorganic phosphorus (P) added alone or in combination. Cell division rates of C. raciborskii were only statistically higher than the control on day 5 when U and P were co‐supplied. In contrast, cell quotas of CYNs (QCYNS) increased significantly in treatments where P was supplied, irrespective of whether N was supplied, and this increase was not necessarily related to cell division rates. Increased QCYNS did correlate with an increase in the proportion of the cyrA toxin gene to 16S genes in the C. raciborskii‐dominated cyanobacterial population. Therefore, changes in strain dominance are the most likely factor driving differences in toxin production between treatments. Our study has demonstrated differential effects of nutrients on cell division and strain dominance reflecting a C. raciborskii population with a range of strategies in response to environmental conditions.